Кістень з поселення VIII-X ст. в Рідківцях - Калініченко, Віталій; Пивоваров, Сергій; Ільків, Микола (Київ, видавець Олег Філюк, 2018)
The article is devoted to the detailed analysis of rare finds, which relates to the shock weapons of melee combat medieval warrior, namely flail. It was found at a settlement in the village Ridkivtsi in Bukovina, which, according to the accompanying inventory, is chronologically dated VIII-X centuries. This flail is unique for the region, because this kind of finding (for different structural and morphological parameters and specific characteristics) happened here for the first time. In addition, the authors carry out its classification and interpretation. Based on the material found on the settlement, it was found that the flail has a nomadic origin, and it was belonged, obviously, to a hungarian light-armed rider
The Flail found in the settlement of VIII–X Centuries in Ridkivtsi
Keywords: середньовіччя; предмети озброєння; Буковина; археологічні дослідження; кістень